Management of Severely Rotated Anterior Teeth Using Different Techniques in Mixed Dentition - A Report of Two Cases - Shrestha , Neha; Upadhyay, Sumita; Luintel, Sanjeev; Shrestha, Rasna; Dallakoti, Parayash (Journal of Nepalese Association of Pediatric Dentistry, 2023)
One of the most prevalent issues in orthodontics is severe tooth rotation, which is thought to be a developmental phenomenon. Gingival recession, traumatic occlusion, and cosmetic issues can all result from these rotations. Early treatment of these malpositioned teeth could enhance the appearance of the teeth, which would improve the behaviour and self-confidence of the youngsters. This case report shows two cases with anterior teeth rotated roughly by 70 to 90 degrees corrected using fixed appliances at various stages of mixed dentition using two different techniques.